Post-mortem magnetic resonance microscopy (MRM) of the murine brain at 7 Tesla results in a gain of resolution as compared to in vivo MRM - von Bohlen und Halbach, Oliver; Lotze, Martin; Pfannmöller, Jörg P. (Frontiers in Neuroanatomy, 2014)
Small-animal MRI with high field strength allows imaging of the living animal. However, spatial resolution in in vivo brain imaging is limited by the scanning time. Measurements of fixated mouse brains allow longer measurement time, but fixation procedures are time consuming, since the process of fixation may take several weeks. We here present a quick and simple post-mortem approach without fixation that allows high-resolution MRI even at 7 Tesla (T2-weighted MRI). This method was compared to in vivo scans with optimized spatial resolution for the investigation of anesthetized mice (T1-weighted MRI) as well as to ex situ scans of fixed brains (T1- and T2-weighted scans) by using standard MRI-sequences, along with anatomic descriptions of areas observable in the MRI, analysis of tissue shrinkage and post-processing procedures (intensity inhomogeneity correction, PCNN3D brain extract, SPMMouse segmentation, and volumetric measurement). Post-mortem imaging quality was sufficient to determine small brain substructures on the morphological level, provided fast possibilities for volumetric acquisition and for automatized processing without manual correction. Moreover, since no fixation was used, tissue shrinkage due to fixation does not occur as it is, e.g., the case by using ex vivo brains that have been kept in fixatives for several days. Thus, the introduced method is well suited for comparative investigations, since it allows determining small structural alterations in the murine brain at a reasonable high resolution even by MRI performed at 7 Tesla.